Media Relations : issues and strategies - Johnston, Jane, ....- (Sydney : Allen & Unwin, 2013)
Public relations and the media are in a time of major change. The rise of social media, altered media platforms, evolving legislative environments and new models of communication have altered not only the working environments of public relations and the news and entertainment media, but also many aspects of how these industries work together. Media Relations provides a practical and thorough introduction to media work in this changing environment. Based on a solid understanding of media culture and theory, Jane Johnston shows how to steer a path between the technical and human elements of media relations. She drills down into the different types of media, analysing their applications, strengths and weaknesses, and shows how to target your message to the right media outlets, whether national television, community radio, celebrity magazines or influential blogs. This second edition has been revised throughout and includes new case studies, and new chapters on digital and social media, media campaigns, and legal and ethical considerations. 'Media Relations: Issues and Strategies is written in an engaging, easy to understand style. It provides excellent examples and cases of media relations.' - Global Media Journal